2011
DOI: 10.1111/j.1532-5415.2010.03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zolpidem and Sleep Inertia on Balance and Cognition During Nighttime Awakening: A Randomized Placebo-Controlled Trial

Abstract: Zolpidem produced clinically significant balance and cognitive impairments upon awakening from sleep. Because impaired tandem walk predicts falls and hip fractures and because impaired cognition has important safety implications, use of nonbenzodiazepine hypnotic medications may have greater consequences for health and safety than previously recognized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 57 publications
3
46
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to test these particular spatial and temporal aspects of gait performance during a forced nocturnal awakening in late middle-aged and older adults; however, our standing balance findings are in contradiction to those previously reported. 17,18 These findings are contrary to two previous studies in which Frey et al 17 found balance was not impaired during a nocturnal awakening on the difficult tandem walking task and Zammit et al 18 reported no dynamic standing balance impairments as measured using a force plate during a nocturnal awakening. These studies were consistent with ours in participant health and age, and that the nocturnal awakenings all took place about 2 h after habitual sleep time; however, all studies used different equipment, methods, and measured different output parameters.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…To the best of our knowledge, this is the first study to test these particular spatial and temporal aspects of gait performance during a forced nocturnal awakening in late middle-aged and older adults; however, our standing balance findings are in contradiction to those previously reported. 17,18 These findings are contrary to two previous studies in which Frey et al 17 found balance was not impaired during a nocturnal awakening on the difficult tandem walking task and Zammit et al 18 reported no dynamic standing balance impairments as measured using a force plate during a nocturnal awakening. These studies were consistent with ours in participant health and age, and that the nocturnal awakenings all took place about 2 h after habitual sleep time; however, all studies used different equipment, methods, and measured different output parameters.…”
Section: Discussioncontrasting
confidence: 56%
“…These studies were consistent with ours in participant health and age, and that the nocturnal awakenings all took place about 2 h after habitual sleep time; however, all studies used different equipment, methods, and measured different output parameters. Further, Frey et al's 17 walking task was more difficult than our own, and it is possible that alertness circuits were sufficiently activated to more completely awaken their participants, minimizing differences from pre-sleep testing. Zammit et al 18 had fewer participants than our own study (n = 12), and all but one of their participants was female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zolpidem, for example, produces safety significant performance decrements and impaired balance following awakening from sleep. 23 Further, sleep-related eating, sleep walking and sleep driving events have been reported with the use of zolpidem, leading the FDA to require a “black box” warning on all hypnotic medications that driving and performance of other tasks may be impaired in the morning following the use of the such medications: “A variety of abnormal thinking and behavior changes have been reported to occur in association with the use of sedative/hypnotics…. Complex behaviors such as ‘sleep-driving’… have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have shown BZDs to be associated with several adverse clinical outcomes including falls leading to hip fractures [79] and functional decline [5]. Studies have also shown nBZRAs to be associated with an increased risk of hip fracture [10,11] and impaired balance [1214]. Additionally, studies in recent years have suggested that the use of these sedative-hypnotic agents may be associated with serious injuries necessitating emergency treatment [15,16].…”
Section: Introductionmentioning
confidence: 99%